2008
DOI: 10.1098/rsta.2008.0226
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning experiments in the laser-heated diamond anvil cell: volatile content in the Earth's core

Abstract: The present state of the Earth evolved from energetic events that were determined early in the history of the Solar System. A key process in reconciling this state and the observable mantle composition with models of the original formation relies on understanding the planetary processing that has taken place over the past 4.5 Ga. Planetary size plays a key role and ultimately determines the pressure and temperature conditions at which the materials of the early solar nebular segregated. We summarize recent dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…The partition coefficient of He is found to be ∼9 × 10 −3 , in close agreement with the most recent laser-heated diamond-anvil cell experiments (25), but disagrees with earlier data based on piston and cubic anvil press experiments (26), which is 10 −4 when extrapolated to 10 GPa. For an exchange reaction between two phases, the reaction constant, which is the ratio of the activities of the products to those of the reactants, does not change at a fixed temperature and pressure.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The partition coefficient of He is found to be ∼9 × 10 −3 , in close agreement with the most recent laser-heated diamond-anvil cell experiments (25), but disagrees with earlier data based on piston and cubic anvil press experiments (26), which is 10 −4 when extrapolated to 10 GPa. For an exchange reaction between two phases, the reaction constant, which is the ratio of the activities of the products to those of the reactants, does not change at a fixed temperature and pressure.…”
Section: Resultssupporting
confidence: 52%
“…Thus, care should be taken when comparing and using partition coefficients that have been obtained at very different concentration ranges. For example, the two experiments mentioned above (25,26) were performed at very different He concentrations, which might explain the different partition coefficients.…”
Section: Resultsmentioning
confidence: 99%
“…It remains to be checked whether there is strong helium diffusion effect in other silicate glasses and liquids. It has been reported that there could be discontinues drops of noble gas solubility in the silicate melt at certain threshold pressures (35)(36)(37). Our results from the glasses may have implications for the melt.…”
Section: Resultsmentioning
confidence: 62%
“…core pumping of Pb) will need to be critically evaluated. And the helium partition coefficient of ~10 -2 makes the core a plausible source of primordial helium alternative to the undifferentiated lower mantle [8].…”
Section: Discussionmentioning
confidence: 99%
“…Boyet and Carlson [4][5] Sm has decayed away. Since the work of Boyet and Carlson [4][5], the paradigm of "chondritic" mantle has been shifting to a superchondritic mantle [6][7][8]. Assuming a superchondritic mantle would mean that the bulk silicate Earth composition obtained in previous studies and applied to make many inferences about mantle depletion and igneous rock petrogenesis have to be assessed, and there is no easy way to obtain the refractory lithophile element concentrations in BSE unless it can be specified how the superchondritic composition was derived and how the concentrations of the refractory lithophile elements are related.…”
Section: Introductionmentioning
confidence: 99%